2014
DOI: 10.1037/a0036632
|View full text |Cite
|
Sign up to set email alerts
|

Navigating underrepresented STEM spaces: Experiences of Black women in U.S. computing science higher education programs who actualize success.

Abstract: Women in the United States have long been underrepresented in computing science disciplines across college campuses and in industry alike (Hanson, 2004;Jackson & Charleston, 2012). This disparity is exacerbated when African American women are scrutinized. Additionally, prior research (e.g., Hanson, 2004;Jackson & Charleston, 2012;Jackson, Gilbert, Charleston, & Gosha, 2009) suggests a need to better understand this underrepresented group within computing-a field in dire need of additional skilled workers. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 23 publications
5
100
0
4
Order By: Relevance
“…Acknowledging both sides of the vulnerability spectrum presents a more holistic point of view regarding Black women’s identity in STEM. Additionally, with previous scholars sharing that Black women persist in the face of their opposition (e.g., Charleston et al, ; Espinosa, ; Ong, ; Ong et al, ), we find that our participants specifically articulate their intersectional Black woman identity to mean resilience and persistence. Their expressed meaning of their identity demonstrates a potential relationship between their race and gender and their STEM persistence, that not only supports the notion of their intersectional Black woman identity as being protective and even promotive of their STEM engagement, but also provides evidence for the need to further explore the relationship between a positive‐protective identity expression and continued STEM engagement for Black women.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Acknowledging both sides of the vulnerability spectrum presents a more holistic point of view regarding Black women’s identity in STEM. Additionally, with previous scholars sharing that Black women persist in the face of their opposition (e.g., Charleston et al, ; Espinosa, ; Ong, ; Ong et al, ), we find that our participants specifically articulate their intersectional Black woman identity to mean resilience and persistence. Their expressed meaning of their identity demonstrates a potential relationship between their race and gender and their STEM persistence, that not only supports the notion of their intersectional Black woman identity as being protective and even promotive of their STEM engagement, but also provides evidence for the need to further explore the relationship between a positive‐protective identity expression and continued STEM engagement for Black women.…”
Section: Discussionsupporting
confidence: 80%
“…A STEM identity is an expressed association between one’s self and STEM that is contingent upon the individual’s belief in their capabilities within and their conceptual and practical knowledge of their particular STEM discipline (Charleston et al, ; Gainor & Lent, ; Hunter, Laursen, & Seymour, ; Hurtado, Cabrera, Lin, Arellano, & Espinosa, ; Lent et al, ; McGee & Martin, ). A STEM identity is contingent upon the recognition of self as being a competent participant in STEM but also the recognition by others as such (Carlone & Johnson, ; Martin, ).…”
Section: Research On Black Females and Stemmentioning
confidence: 99%
“…Studies want to know why women are successful on campus as faculty (Olund 2012) and for degree completion (George-Jackson 2009). Success for women in underrepresented groups (Alexander Nealy 2017; Charleston et al 2014) is a growing area of literature as well. It is not enough that women persist through programs and quietly graduate; they must be successful (Whalen and Shelley 2010).…”
Section: Persistencementioning
confidence: 99%
“…Thus, considering these narratives in light of the reality that Canada remains largely a settler (or resettler, if you consider what LaRocque [2015] has to say on this) society, we might conclude that Elby, Mae, and Kaybe's feelings of estrangement are reflective of persistent social patterns or habits that have sought to systemically, and often forcibly, detach Indigenous people from their cultures and identity. This is echoed in the passages below: These experiences of estrangement echo research that explores the experiences of underrepresented racial/ethnic minority students studying at predominately white institutions (PWIs) in the U.S. (Bourke, 2010;Charleston, George, Jackson, Berham, & Amechi, 2014;Gusa, 2010;White & Lowenthal, 2011;Quaye, Tambascia, & Talesh, 2009). For instance, Quaye, Tambascia, and Talesh suggest that, not unlike Mae, Elby, Em, and Kaybe, African American students who study in PWIs often experience a sense of alienation and isolation as a result of being "one of few" (p. 160) in the classroom.…”
Section: Academic Writing As Estrangementmentioning
confidence: 93%
“…Although the institution in which this research takes place does not release data that directly indicates it is a PWI, it has noted that Indigenous students make up roughly 9% of the university population 7 . At any rate, Charleston, George, Jackson, Berham, and Amechi (2014) argue that predominately White institutional culture has a significant impact on underrepresented populations, and all too often the onus is put on students to adapt and adopt predominately White norms that seem to require students to "divorce their cultures and identities from the learning process" (Quaye, Tambascia, & Talesh, 2009, p. 158). This need not be explicit either; Black students have reported that racism is often "frequently embedded in the culture of the university" and the classroom (Gusa, 2010, p. 466).…”
Section: Pwis Whiteness and White Privilegementioning
confidence: 99%